A novel 53 kDa protein (BoP53) in Babesia orientalis poses the immunoreactivity using the infection serum. (October 2020) - Shu, Xiang; Guo, Jiaying; Nie, Zheng; Xia, Yingjun; He, Lan; Zhao, Junlong
Abstract: Babesia orientalis ( B. orientalis ) is responsible for water buffalo babesiosis, which caused serious economic losses in the south of China. Although the invasion process has been roughly described, there are still some unknown molecules that have not yet been identified. Recently, an invasion-related protein BOV57 has been identified in the Babesia bovis . However, there is no report available about the gene in B. orientalis . B. orientalis P53 (BoP53) sequence was obtained by blast BOV57 sequence in B. orientalis genome database, and the full length of the BoP53 gene is 1599 bp. BoP53 gene was cloned into a pGEX-6P-1 expression vector and expressed as a GST-tag fusion protein. The tertiary structure of BoP53 was predicted with the I-TASSER software. The native BoP53 was identified from of B. orientalis lysate incubation with mouse antiserum against rBoP53. BoP53 as a novel identified protein promotes the study of B. orientalis, the reaction of rBoP53 with the serum of B. orientalis -infected water buffalo but not with healthy buffalo serum indicated its good antigenicity. It may be a candidate antigen for the diagnosis of B. orientalis infection.